In-silico Analysis of Human miRNAs in SARS-CoV-2 Genome - Syed Hassan Abbas; Muhammad Tariq Pervez; Amera Ramzan; Muhammad Xaaceph Khan (BioScientific Review, 2021)
In December2019, a new coronavirus(SARS-CoV-2) was discovered in Wuhan (China)that was rapidly transmittedto many other countries. Henceforth, the World Health Organization (WHO) Emergency Committee declared a global health emergency on January30, 2020. Statistics depictedthe fatality rate as about 1.4%. In this study, a potential antiviral treatment for the SARS-CoV-2 virus using host miRNAs was explored which may slow down the expression of viral genes to suppress viral replication.The miRNAsfrom genome (coronavirus/SARS-CoV-2) were analyzed using various computational approaches.The complete genome sequence was retrieved from NCBI. The result of our study highlighted that hsa-miR-3675-3p (MD19), hsa-miR-363-5p (MD220), hsa-miR-325 (MD306), hsa-miR-2114-5p (MD306), hsa-miR-744-3p (MR186) and hsa-miR-448 (MR186)can be used as an antiviral treatment to quell the replication of SARS-CoV-2virusin humanbeings.Thefindings and observations of our study openednew possibilitiesto explore both the pathogenesis function of miRNAsand for the development of novelantiviral drugs.Keywords: genome, hybridization, In silico, miRNAs, SARS-CoV-2 GenomeCopyright (c) The Authors